Analisis Faktor-Faktor yang Mempengaruhi Permintaan Air Minum PDAM Tirta Sakti Kerinci - Wiyan Mailindra; Azwar Anas (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
This research was carried out using quantitative descriptive method. to determine the factors that affect demand for drinking water PDAM Tirta Sakti Kerinci regency during the years 2003-2017 used multiple linear regression model with melogaritmakan model. From the calculation by using SPSS version 12.0 was obtained coefficient of determination (R2) of 0.984, which means that the model is able to explain the total variation in demand caused by the variable Per Capita Income, Price Water, Number of Customers and Production. From the result, known that variable-free variables Per Capita Income, Price Water, Total Customer and production significantly influence the dependent variable was the demand of drinking water. But if we see a partial, then only the per capita income variable, the variable price of water and production variables that significantly influence the dependent variable was the demand of drinking water. This was seen from test results where the t-calculated t = 3.098> 1.812 but has a negative direction for variable income per capita, t-count = 2.475> t-table value = 1.812 for the variable price of water and t-calculated value = 4.805> t -table = 1.812 for the variable production, because t count> t-table, so Ho is rejected. This means that the variable of per capita income, water price variable and the variables significantly affect the production of variable demand (consumption) of drinking water on the PDAM Tirta Sakti Kerinci district.